A SURVEY-BASED ANALYSIS OF HEALTHCARE PROFESSIONALS’ PERSPECTIVES ON THE CLINICAL INTEGRATION OF AI-DRIVEN HEALTH APPLICATIONS IN PAKISTAN (The Research of Medical Science Review, 2025)
Objective: To assess healthcare professionals’ awareness and usage of AI-driven health applications, explore their perceptions of benefits and limitations, and identify barriers and facilitators to clinical adoption in Pakistan.Methods: A cross-sectional survey was conducted among 350 healthcare professionals, medical students, and AI conference attendees from POF Hospital and WMC in Pakistan, selected via purposive sampling. Data were collected using a standardized questionnaire based on the Technology Acceptance Model (TAM), assessing demographics, AI usage, perceived usefulness, ease of use, and barriers/facilitators. Descriptive and inferential statistics were analyzed using SPSS.Results: Most participants were aged 31–40 (58.9%), female (71.4%), and held undergraduate degrees (81.1%), with 57% from medicine and 31.1% from nursing. AI usage was moderate, with 58.3% of medical professionals and 63.3% of nurses reporting adoption. Perceived usefulness scored 3.64 (SD = 1.25), ease of use 3.05 (SD = 1.01), and technology familiarity 2.61 (SD = 0.74), indicating basic to intermediate digital literacy. Major barriers included data security concerns (86.0%), time constraints (33.7%), and lack of training (30.0%), while facilitators were accessibility (65.1%), trust in apps (60.3%), and reliability (55.7%).Conclusion: Pakistani healthcare professionals show moderate AI adoption with positive perceptions of its usefulness but face significant barriers like data security concerns and limited training. Enhancing digital literacy, strengthening data privacy frameworks, and integrating AI education into medical curricula are critical to advancing AI-driven health integration in Pakistan..